Interpretasi Riqāb, Gārimīn, Fī Sabīlillāh dan Ibn Sabīl Menjadi Kepentingan Umum Sebagai Mustahik Zakat (Studi Pemikiran Yūsuf al-Qaraḍāwī) - Makraja, Fahmi; Azmi, Ulil (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2024)
The majority of scholars agree that the recipients of zakat are those who have been mentioned in the Qur'an and not to others such as infrastructure, irrigation, bridges and other public facilities because theoretically this is not included in the mustahik zakat. A contemporary scholar named Yūsuf al-Qaraḍāwī looked at every problem carefully, prioritized the element of benefit, and adjusted to the development of the times and circumstances, including classifying the public interest as mustahik zakat. The purpose of this research is to find out Yūsuf al-Qaraḍāwī's thoughts on the public interest as mustahik zakat, which is analogous to riqāb, muallaf, gārimīn, fī sabīlillāh, and ibn sabīl, and to find out what the basis of this interpretation is. This study uses a qualitative research method by examining various sources related to the object being studied based on library research. The data collection method is carried out by looking for literature sources that are relevant to the study and then reviewing and analyzing them. The results of the study show that Yūsuf al-Qaraḍāwī interpreted that the public interest included in the part of the zakat recipients is the result of analogies in riqāb, muallaf, gārimīn, fī sabīlillāh, and ibn sabīl. Yūsuf al-Qaraḍāwī's interpretation of mustahik zakat by classifying it into two categories, namely the first four and the last four. Yūsuf al-Qaraḍāwī is of the view that the last four mustahik zakat include general benefits that are in accordance with the development of the times.